Предмет: Алгебра,
автор: maxmova
упростите выражение {-2аb}^3*{3a}^2*{b}^4
Ответы
Автор ответа:
0
{-2аb}^3*{3a}^2*{b}^4 =
= {-2}^3*{а}^3*{b}^3*{3}^2*{a}^2*{b}^4=
=-8*9 a^(3+2) * b^(3+4) =
= -72 *a^5 *b^7
= {-2}^3*{а}^3*{b}^3*{3}^2*{a}^2*{b}^4=
=-8*9 a^(3+2) * b^(3+4) =
= -72 *a^5 *b^7
Автор ответа:
0
(-2ab)^3 * (3а)^2 * b^4 = -8a^3b^3 * 9a^2 * b^4 = -72a^5b^7
Похожие вопросы
Предмет: Математика,
автор: l1mbo66
Предмет: Биология,
автор: RobiyaShams
Предмет: Физика,
автор: mpavluk36
Предмет: Математика,
автор: мурас